THE ROLE OF SHARIA FINANCIAL INSTITUTION TO EMPOWERING SMEs - Jamaluddin, Jamaluddin; Abdullah, M. Wahyuddin (Jurnal Iqtisaduna, 2019)
This study aims to determine the efforts of Islamic Financial Institutions in empowering SMEs, strategies and important roles carried out by LKS in order to empower SMEs through the provision of capital to be managed in business. The method used in this research is descriptive analysis method, a method that only describes various forms of paradigms about empowerment strategies for SMEs, the most important data sources in this study are related to the search for library data, relevant books, and scientific papers. others relevant to the object of study. The results of this study indicate that there has been much power and effort carried out by the Islamic Finance Agency in order to empower SMEs, this can be proven by the existence of several programs, products, and financing aimed directly at SMEs. The strategy used is; provide complete information as well as promotion to SMEs, provide financing for their business development, provide financing in accordance with the type of business that SMEs are involved in with the concept of sharia principles. The implication of this research is to continue to provide services professionally and provide the best so that they are truly able to provide community welfare, more selective in providing financing so as to minimize the losses that will occur, increase technological resources so that SMEs can easily access information.